Comparison of Primary Molar Crown Dimensions with Stainless Steel Crowns in a Sample of Iranian Children - Hossein Afshar; Arghavan Kamali Sabeti; Mahdi Shahrabi (Tabriz University of Medical Sciences, 2015)
Background and aims. Due to anatomic variation in tooth anatomy between populations, this study compared the buccolingual (BL) and mesiodistal (MD) dimensions of primary molars with those of stainless steel crowns (SSCs) in anIranian population. Materials and methods. Impressions were taken from both dental arches of children, and casts were poured. Teeth with caries, restoration, hypoplasia or other dental anomalies were excluded. 216 primary molars were selected and divided into 4 groups of 54 each (maxillary and mandibular first and second primary molars). MD/BL dimensions were measured using a digital caliper with 0.01 mm precision on casts and SCCs (3M brand). Data were assessed using paired t-test, post hoc test and ANOVA. P < 0.05 was considered statistically significant. Results. The MD dimension of the lower first molar SSC and the BL dimension of the lower second molar SSC had the least difference with the corresponding values of the respective teeth. The MD dimension of the upper second molar SSC and the BL dimension of the upper first molar SSC had the greatest difference with the corresponding values in the respective teeth. Comparison of the two different brands of SSCs for the upper first molar revealed that both types had significant differences with the teeth in terms of both MD (P = 0.0) and BL (P = 0.0) dimensions. Conclusion. In the studied population, best adaptation was seen in second lower molars and the least adaptationswere seen in first and second upper molars.